الذاكرة بين التجربة والرؤية وأدوات التنصيص الشعري: Memory in the light of Experience, Vision and Poetic Principles - Ayman Muhammad Ali Maidan, ayman (Al Manhal Research Journal, 2021)
Memory has a strong hold on human life.it acts as a bridge between past and the future, because future framed in one the basis of past experience. Memorization is a constant and dynamic factor. In literature writers and poets depend upon their memories. Particularly Arabic language classical poetry reflects their past. In this article author has explained as to how memory affected the psychology of poets in the field of literature. Author has also pointed out different factors influencing memory to make their poetry forceful.